Cover Image, Volume 42, Issue 5. (15th March 2018) - Bai, Zhang; Sun, Jie; Liu, Qibin
Abstract : The cover image, by Zhang Bai et al., is based on the Research Article Comprehensive assessment of line‐/point‐focus combined scheme for concentrating solar power system, DOI:10.1002/er.3997 .